Stranger - Brown, Rachel Manija (Viking, an imprint of Penguin Group (USA), 2014)
"Generations after an unknown Change eliminated electricity and gave people unusual powers, the Southern Californian town of Las Anclas must deal with the consequences when a teenage prospector comes to stay"--